On a certain subclass of analytic univalent function defined by using Komatu integral operator - RAHROVI, Samira (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In this paper a certain class of analytic univalent functions in the open unit disk is defined. Some interesting results including inclusion relations argument properties and the e ect of the certain integral operator to the elements of this class are investigated. Mathematics Subject Classification (2010): 30C45.